Design And Building Of A Web Based E-Voting System For The Election Of Osis Chairman At SMPN 10 Bengkulu Selatan Using Rapid Application Development (RAD) Method - Soneta Sulaini; Gunawan Gunawan; Yulia Darmi; Ardi Wijaya; Kirman Kirman (Jurnal Komputer, Informasi dan Teknologi, 2024)
The election of the chairman and deputy chairman of the OSIS is held every year by all schools including SMPN 10 Bengkulu Selatan. The election was carried out conventionally where this activity required quite a lot of money and energy as well as quite long teaching and learning hours which were cut to carry out the election of the OSIS chairman. Apart from that, there is the potential for fraud, human error, operational inefficiencies from the start to the end of the election, and non-real-time monitoring which are shortcomings of conventional voting systems. To answer this problem, research is proposed which aims to build a web-based e-voting system for the election of OSIS chairman at SMPN 10 Bengkulu Selatan. The software development method used is Rapid Application Development (RAD). The method emphasizes rapid and incremental prototyping.